Jordan K. answered • 09/25/15

Nationally Certified Math Teacher (grades 6 through 12)

Hi Ruby,

Let's begin by writing the standard form of the quadratic equation:

ax

^{2}+ bx + c = 0Next, let's write the quadratic formula:

x = [-b +/- √(b

^{2}- 4ac)] / 2aNow, let's see what are our coefficients (a, b, c) are in our given equation using the standard form of the quadratic equation:

ax

^{2}+ bx + c = 0 [standard form] 3p

^{2}+ 7p + 4 = 0 [our variable is p instead of x] a=3; b=7; c=4

Let's plug in our values for a, b, c into the quadratic formula and solve for p:

p = [-b +/- √(b

^{2}- 4ac)] / 2a p = [-7 +/- √(7

^{2}- 4(3)(4)] / 2(3) p = [-7 +/- √(49 - 48)] / 6

p = [-7 +/- √1] / 6

p = [-7 +/- 1] / 6

**p**= (-7 + 1)/6 = -(6/6) =

**-1**

**p**= (-7 - 1)/6 = -(8/6) =

**-(4/3)**

Thanks for submitting this problem and glad to help.

God bless, Jordan.